Analisis Dampak Pengembangaan Objek Wisata Religi Dalam Meningkatkan Pendapatan Masyarakat:: Studi Kasus Desa Babussalam Besilam Kabupaten Langkat - Faridani Faridani; Muhammad Arif; Khairina Tambunan (Economic Reviews Journal, 2023)
Langkat Regency has potential tourism potential to be developed. One of the tourist attractions that are often visited by visitors is the Babussalam Besilam Religious Village. Various efforts have been made by the local government to attract the attention of tourists to visit Langkat Regency, including the development of its tourism sector. This study aims to find out, firstly how to develop religious tourism objects in Babussalam Besilam village, secondly to find out the impact of developing religious tourism objects in increasing community income. The research approach carried out in this study is descriptive qualitative with data collection methods using observation, interviews and documentation techniques. The results of the study concluded that First, the development carried out on the Religious Tourism Object of Babussalam Besilam Village. The cooperation carried out by the provincial government with the village government to build facilities and infrastructure such as mosques, fields, UMKM business stalls, roads and drainage construction, both The existence of this tourist attraction has a positive impact on the surrounding community they can take advantage of existing opportunities for entrepreneurship and create fields work, although religious tourism objects have a positive impact, it does not increase people's income, although visitors who come every day are crowded, but most visitors who come only for pilgrimages, convey their wishes or participate in other religious activities. both the local government and religious tourism administrators to optimize the facilities and infrastructure of religious tourism objects that have not been held, make supporting facilities so that religious tourism objects are not monotonous and traders should create new products in the future. his master. Keywords: Tourism Development, Religious Tourism, Community Income